Finite element analysis of sagittal screw expander appliance in the treatment of anterior maxillary hypoplasia - Zhang, Jian; Liu, Caiyun; Dong, Yan (Frontiers in Bioengineering and Biotechnology, 2023)
The skeletal anterior crossbite is a common malocclusion in clinic. However, there have been no reports on the maxillary sagittal expansion to correct the premaxillary hypoplasia, which greatly influences the facial morphology and masticatory function, using finite element analysis. In the present study, a three-dimensional finite element model of craniomaxillofacial complex with maxillary sagittal hypoplasia is constructed and the treatment for premaxillary hypoplasia by the sagittal screw expander appliance is simulated. The hypoplasia of the left premaxilla is more serious than that of the right and thus the size of the left part of premaxillary expander baseplate is designed to be larger than that of the right part and the loading is applied at 10° leftward to the sagittal plane and 30° forward and downward to the maxillary occlusal plane. The displacements or equivalent stress distributions of the maxilla, teeth and their periodontal ligaments, are analyzed under the loads of 5.0 N, 10.0 N, 15.0 N, and 20.0 N. Consequently, as the load increases, the displacements or equivalent stresses of the maxilla, teeth and their periodontal ligaments all increase. Almost the whole premaxilla markedly move forward, downward, and leftward while other areas in the craniomaxillofacial complex remain almost static or have little displacement. The equivalent stress concentration zone of the maxilla mainly occurs around and in front of the incisive foramina. The displacements of left premaxilla are generally greater than those of the right under the loading forces. The maximum equivalent stress on the teeth and their periodontal ligaments are 2.34E-02 MPa and 2.98E-03 MPa, respectively. Taken together, the sagittal screw expander appliance can effectively open the premaxillary suture to promote the growth of the premaxilla. An asymmetrical design of sagittal screw expander appliance achieves the asymmetric expansion of the premaxilla to correct the uneven hypoplasia and obtains the more symmetrical aesthetic presentation. This study might provide a solid basis and theoretical guidance for the clinical application of sagittal screw expander appliance in the efficient, accurate, and personalized treatment of premaxillary hypoplasia.